Enhancement of versatile extracellular cellulolytic and hemicellulolytic enzyme production by Lactiplantibacillus plantarum RI 11 - Mohamad Zabidi, Nursyafiqah Athirah (2021)
Recently, lactic acid bacteria (LAB) isolated from Malaysian foods have been shown to have the capability to produce versatile extracellular proteolytic, cellulolytic and hemicellulolytic activities. Approximately 15% of agricultural waste rich in cellulosic biomass is generated annually, causing major disposal problem in Malaysia. Following the “waste-to-wealth” initiative, these inexhaustible renewable biomasses can be utilise for the production of cellulolytic and hemicellulolytic enzymes. These enzymes, in return, can be used to degrade the cellulosic biomass into high value-added products. Therefore, the main objective of this study is to enhance versatile extracellular cellulolytic and hemicellulolytic enzyme production by L. plantarum RI 11 using renewable agrowaste and to purify and characterise selected extracellular endoglucanase produced by L. plantarum RI 11. Different agricultural wastes involved were molasses, rice straw and soybean pulp with glucose and yeast extract as control ingredients. Out of 6 lignocellulosed-based media, basal media consisted of the combination of molasses and yeast extract; M3 (log 10.51 CFU/mL) and combination between molasses and soybean pulp; M4 (log 10.51 CFU/mL) produced the highest cell biomass while producing the highest specific enzyme activities over a broad pH range. This indicate that the cell viability and the production of extracellular cellulolytic and hemicellulolytic enzymes were induced by different cellulosic substrates. Subsequently, statistical optimisation approach of Fractional Factorial Design (FFD) was employed to enhance the cell biomass and extracellular cellulolytic and hemicellulolytic enzyme productions by L. plantarum RI 11. Out of the 16 formulated media, basal media with molasses, yeast extract and soybean pulp (F4 medium) and rice straw, yeast extract and soybean pulp (F5 medium) produced the highest cell biomass of log 11.76 CFU/mL, whereas F12 medium supplemented with glucose, molasses and PKC enhanced extracellular endoglucanase (43.91 μg/min/mg), exoglucanase (26.10 μg/min/mg) and mannanase (10.26 μg/min/mg) specific activities significantly at various pH range. Due to the highest specific activity of endoglucanase produced by using F12 medium, it was subsequently purified to apparent homogeneity by using Fast Protein Liquid Chromatography System. Strategy B was established as the best strategy as the purification fold of 2.17-fold at pH 5, 3.37-fold at pH 6.5 and 2.14-fold at pH 8. The native molecular mass of the purified endoglucanase was estimated to be 120 kDa by gel filtration chromatography, whereas 20 kDa peptide band was detected by Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) inferring that the extracellular endoglucanase enzyme was probably comprised 6 subunits of 20 kDa peptide molecules. In conclusion, L. plantarum RI 11 had the capability to produce versatile extracellular cellulolytic and hemicellulolytic enzymes by using various renewable polymers. Therefore, L. plantarum RI 11 is a promising and versatile bio-transformation agent to degrade lignocellulolytic biomass.